Analisa Fundamental Makro, Struktur Kepemilikan, Fundamental Mikro Terhadap Nilai Perusahaan dengan Manajemen Laba, Kinerja Keuangan dan Karakteristik Perusahaan sebagai Variabel Intervening pada Perusahaan Properti dan Real Estate Periode 2019-2023 - Jannah, Arizza Zulia Rahmatul; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study aims to see how the impact of Macro Fundamentals, Ownership Structure, Micro Fundamentals on Company Value with Profit Management, Financial Performance and Company Profile as Intervening Variables in Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period. This study applies quantitative methods and applies secondary data obtained from the observation of the annual reports of Property and Real Estate Companies listed on the Indonesia Stock Exchange for the 2019-2023 period through the Company's www.idx.co.id and internet pages. The samples used were 6 Property and Real Estate Companies which were taken by applying a purposive sampling approach, then processed to apply the Smart-PLS version 4 application. The findings of this study say that Macro Fundamentals, Micro Fundamentals and Ownership Structure do not have a significant impact on the Company's Profile. Then Macro Fundmental, Micro Fundamentals, Ownership Structure, Company Profile and Profit Management do not have a significant impact on Financial Performance. Furthermore, Macro Fundamentals, Micro Fundamentals and Ownership Structure do not have a significant impact on Profit Management. Then Micro Fundamentals, Company Profile, Financial Performance, Profit Management and Ownership Structure do not have a significant impact on Company Value, while Macro Fundamentals have a significant impact on Company Value.